Nuclease‐mediated genome editing: At the front‐line of functional genomics technology. (5th January 2014) - Sakuma, Tetsushi; Woltjen, Knut
<x xml:space="preserve">Abstract</x> Genome editing with engineered endonucleases is rapidly becoming a staple method in developmental biology studies. Engineered nucleases permit random or designed genomic modification at precise loci through the stimulation of endogenous double‐strand break repair. Homology‐directed repair following targeted DNA damage is mediated by co‐introduction of a custom repair template, allowing the derivation of knock‐out and knock‐in alleles in animal models previously refractory to classic gene targeting procedures. Currently there are three main types of customizable site‐specific nucleases delineated by the source mechanism of DNA binding that guides nuclease activity to a genomic target: zinc‐finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs), and clustered regularly interspaced short palindromic repeats (CRISPR). Among these genome engineering tools, characteristics such as the ease of design and construction, mechanism of inducing DNA damage, and DNA sequence specificity all differ, making their application complementary. By understanding the advantages and disadvantages of each method, one may make the best choice for their particular purpose.